Polymorphisms indicating risk of inflammatory bowel disease or antigenicity to anti-TNF drugs as biomarkers of response in children - Paula Zapata-Cobo; Sara Salvador-Martín; Marta Velasco; Laura M. Palomino; Susana Clemente; Oscar Segarra; Ana Moreno-Álvarez; Ana Fernández-Lorenzo; Begoña Pérez-Moneo; Montserrat Montraveta; Cesar Sánchez; Mar Tolín; et al. (Elsevier, 2023)
Few genetic polymorphisms predict early response to anti-TNF drugs in inflammatory bowel disease (IBD), and even fewer have been identified in the pediatric population. However, it would be of considerable clinical interest to identify and validate genetic biomarkers of long-term response. Therefore, the aim of the study was to analyze the usefulness of biomarkers of response to anti-TNFs in pediatric IBD (pIBD) as long-term biomarkers and to find differences by type of IBD and type of anti-TNF drug. The study population comprised 340 children diagnosed with IBD who were treated with infliximab or adalimumab. Genotyping of 9 selected SNPs for their association with early response and/or immunogenicity to anti-TNFs was performed using real-time PCR. Variants C rs10508884 (CXCL12), A rs2241880 (ATG16L1), and T rs6100556 (PHACTR3) (p value 0.049; p value 0.03; p value 0.031) were associated with worse long-term response to anti-TNFs in pIBD. DNA variants specific to disease type and anti-TNF type were identified in the pediatric population. Genotyping of these genetic variants before initiation of anti-TNFs would enable, if validated in a prospective cohort, the identification of pediatric patients who are long-term responders to this therapy.